2016
DOI: 10.3892/etm.2016.3515
|View full text |Cite
|
Sign up to set email alerts
|

Effect of various doses of vitamin D supplementation on pregnant women with gestational diabetes mellitus: A randomized controlled trial

Abstract: It has previously been reported that the influence of vitamin D on the metabolism of calcium and phosphorus is associated with diabetes, cardiovascular disease, Alzheimer's disease, cancer and other systemic diseases, and is considered an important indicator of general health. The present study was conducted to determine the effect of various doses of vitamin D supplementation on glucose metabolism, lipid concentrations, inflammation and the levels of oxidative stress of pregnant women with gestational diabete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 35 publications
6
60
1
Order By: Relevance
“…In our study, vitamin D 3 consumption also decreased serum triglyceride while could not improve other serum lipid components. Contrary to our ndings, Asemi et al, and Zhang et al, reported that cholecalciferol intake decreased the level of total cholesterol; however, it displayed no signi cant effect on serum triglyceride, LDL-C and HDL-C levels (25,29). Moreover, in a study on overweight and obese participants, intake of cholecalciferol supplement for a period of one year did not reduce any components of the lipid pro le (31).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In our study, vitamin D 3 consumption also decreased serum triglyceride while could not improve other serum lipid components. Contrary to our ndings, Asemi et al, and Zhang et al, reported that cholecalciferol intake decreased the level of total cholesterol; however, it displayed no signi cant effect on serum triglyceride, LDL-C and HDL-C levels (25,29). Moreover, in a study on overweight and obese participants, intake of cholecalciferol supplement for a period of one year did not reduce any components of the lipid pro le (31).…”
Section: Discussioncontrasting
confidence: 99%
“…Low, medium, and high doses of vitamin D supplementation did not reduce FPG. Similar to our study, they reported a decrease in serum insulin and HOMA-IR levels in groups receiving medium and high doses of vitamin D supplements (29). In another study, insulin resistance decreased in patients with GDM who received 50000 IU vitamin D, every 2 weeks from the 12th week of pregnancy up to delivery (higher vitamin D3 dose and the duration are comparable with our study) (30).…”
Section: Discussionsupporting
confidence: 90%
“…In addition, vitamin D supplementation at a dosage of 60,000 IU/month for 3 months in subjects with rheumatoid arthritis significantly decreased CRP concentrations [38]. In another study, Zhang et al [39] observed significant increases in TAC and GSH levels following the intake of high-dose vitamin D (50,000 IU every 2 weeks) for 12.5 days among women with gestational diabetes. Vitamin D supplementation at a dosage of 200,000 IU for 4 weeks also reduced inflammatory markers and increased TAC levels in elderly women with vitamin D insufficiency [40].…”
Section: Discussionmentioning
confidence: 97%
“…Figure 1 shows the search details of the study selection process and the reasons for exclusion of studies for our systematic review and meta-analysis of vitamin D supplementation in GDM. In total, 6 RCTs [29][30][31][32][33][34] met the inclusion criteria and their full texts were obtained for further review. Upon further scrutiny, 1 of these 6 RCTS, which did not include original data and had less relevant maternal outcomes [34], was excluded from the meta-analysis.…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
“…The studies that met inclusion criteria [29][30][31][32][33][34] were reviewed by the fourth author (F.J.) and the outcomes of these RCTs that could be retained for meta-analysis were considered the primary outcome in this review. Therefore, the primary outcome measures included in this review were mean changes in FPG, Insulin, HOMA-IR, TG, TC, HDL cholesterol, LDL cholesterol, and hs-CRP.…”
Section: The Outcome Measuresmentioning
confidence: 99%